DIVERSITY AND COMPOSITION OF SOIL ARTHROPODE IN THE REVEGETATION AREA OF COAL MINING USED LAND OF PT. BARA ALAM UTAMA, SITE LAHAT, SOUTH SUMATERA - Pujiati, Puput; Lamin, Syafrina; Windusari, Yuanita (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2020)
Coal mining can disrupt the balance of the ecosystem, including the soil environment ecosystem as a habitat for soil arthropods. This study aims to see the soil arthropod family, relative density, diversity, dominance and evenness of soil arthropods in the revegetation area of the ex-mining area of PT. Bara Alam Utama. The re-search was conducted in the revegetation area of the former coal mine area of PT. Bara Alam Utama in Lahat district, South Sumatra. The research area consists of 8 location points, namely natural areas, revegetation areas of age 7,6,5,4,3,2 and 1 year. The study was conducted using an exploratory survey method, sampling was car-ried out based on the purposive sampling method by drawing a 100 m long transect with 5 sample plots inside measuring 20 x 10 m at each revegetation age. The results showed that the highest soil arthropod diversity index was found at the 3 year old revegetation location (H = 0.915) and the highest soil arthropod evenness index was at the 3 year old revegetation location (e = 0.17), while the highest soil arthropod dominance index was at 5 year old revegetation location (D = 0.886) which causes the 5 year revegetation location to have the lowest soil ar-thropod diversity index and evenness index (H = 0.351 and e = 0.054), while the lowest soil arthropod domi-nance index value is at the 3 year old revegetation location (D = 0.667), so it can be seen that there is a correla-tion between the diversity index and the evenness index of soil arthropods where both are inversely proportional to the results of the calculation of the dominance index. The high and low diversity index at each research loca-tion is influenced by abiotic factors (pH, soil temperature and soil moisture), age of revegetation and type of vegetation